2008
DOI: 10.1159/000154248
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Lung Allergic Inflammation and Malnutrition

Abstract: Nutritional deficiency is commonly associated with a significantly impaired immune response, particularly in relation to cell-mediated immunity, the complement system, cytokine production and phagocyte function. However, there are few data on the consequences of nutritional deficiency in allergic diseases of the lung. In fact, malnutrition is the most common cause of immunodeficiency worldwide. Several studies have indicated that the incidence of alterations in lung functions can be associated with birth weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 289 publications
0
2
0
1
Order By: Relevance
“…The proximity of mast cells and eosinophils in allergic inflammation and the fact that they can stimulate each other even in the absence of an exogenously added activator [30][31][32] has generated several hypotheses on a crosstalk between the two cells. In fact, some in vitro studies have suggested possible pathways of soluble cross-talk between these cells [33][34][35][36][37][38].…”
Section: Mast Cells and Eosinophils The Two Components Of ''The Allementioning
confidence: 99%
“…The proximity of mast cells and eosinophils in allergic inflammation and the fact that they can stimulate each other even in the absence of an exogenously added activator [30][31][32] has generated several hypotheses on a crosstalk between the two cells. In fact, some in vitro studies have suggested possible pathways of soluble cross-talk between these cells [33][34][35][36][37][38].…”
Section: Mast Cells and Eosinophils The Two Components Of ''The Allementioning
confidence: 99%
“…Malnutrition is associated with a poor COPD prognosis and may be associated with the development of pulmonary allergic inflammation [25]. Zinc and nitrogen monoxide protect against autoimmunity, cancer, infection, and allergies under Th1 conditions [26].…”
Section: Relationship To Dietmentioning
confidence: 99%
“…Foi também relatada depressão da resposta imune cutânea em testes de hipersensibilidade tardia (CHANDRA, 1997;LANDGRAF et al, 2008), redução do número absoluto de linfócitos T no sangue periférico e diminuição da resposta proliferativa desta população de linfócitos em cultura (SCHAIBLE e KAUFFMAN, 2007). Além disso, a proporção de linfócitos T auxiliadores/indutores (CD4 + ) apresentou-se reduzida, com pouca alteração na subpopulação de células T supressoras/citotóxicas CD8 + (CHANDRA, 1997;CHATRAW et al, 2008).…”
Section: Desnutrição E óRgãos Linfóides Secundáriosunclassified